The Influence of Training, Compensation, and Career Development on Employee Performance at PT Trans Dana Profitri, Bank Indonesia West Java Office - Rizki Agusteen; Irma Nilasari (Dinasti International Journal of Education Management and Social Science, 2025)
This study aims to analyze the influence of job training, compensation, and career development on employee performance at PT Trans Dana Profitri, assigned to the Representative Office of Bank Indonesia, West Java Province. Using a quantitative approach with descriptive and verificative methods, data were collected from 116 employees selected through purposive sampling. Multiple linear regression analysis with SPSS 26 was applied after testing classical assumptions, including a corrective data transformation to ensure normality. The results show that job training, compensation, and career development simultaneously have a significant effect on employee performance. Partially, job training and career development significantly improve performance, while compensation shows no significant effect. The findings strengthen Herzberg’s Two-Factor Theory by highlighting that intrinsic factors, such as competence development and career growth, play a more dominant role than financial rewards. This study contributes theoretically by integrating three HR dimensions within an outsourcing service context.